جزاء المسؤولية المدنية الناشئ عن الخطأ الطبي (Comprehensive Journal of Science, 2025)
The medical profession is considered one of the noblest human professions because it directly affects human life and because the body has a sanctity that requires the person performing medical work to preserve it. Therefore, the work of medicine has become related to the human body and life, as he is one of the people whom God has blessed with intervening in the human body because of the divine secrets it carries to help it heal. The more medical sciences develop, the more necessary the intervention and assistance of those performing medical work increases, and thus the possibility of error increases, as ordinary people are not immune from it. When a medical error occurs, the assessment of compensation for medical damages is a matter necessitated by the need to enlighten doctors about their role, and the role of judges in assessing the damage so that the injured party can obtain his right through appropriate compensation. Compensation may be in kind or compensation for a fee, and the compensation may include material and moral damage. The responsibility is based primarily on the doctor's error and the harm inflicted on the patient, and the latter has the right to recover the harm that affected his physical or moral being, so he finds no escape except to pursue the person responsible judicially.  • The importance of the study on the subject of punishment from civil liability raises several issues, namely the search for the legal basis for the personresponsible for the damage and the relationship between the doctor and the patient in terms of its nature. • I relied on the analytical descriptive approach for the purpose of covering the subject. • Accordingly, the problem is preferable. We relied on evaluating the research into two topics as follows: The first topic: The provisions of civil liability arising from medical error. The first section: Provisions of civil liability arising from medical error.The first requirement: the legal nature of the medical error.The first section: The concept of medical error.Section Two: Characteristics of medical error.The second requirement: Elements of civil liability for medical error.Section One: Medical Error.Section Two: Damage resulting from medical error.Section Three: The causal relationship between error and damage.The second section: The effects of civil liability in medical error.The first requirement: compensation as an effect of civil liability for medical error.Section One: Compensation in kind.Section Two: Cash compensation.The second requirement: the mechanism for estimating compensation.Section One: Judicial compensation.Section Two: Compensation agreed upon as a condition of the penalty.
Keywords: Penalty - Civil Liability - Medical Error - Damage - Compensation